Single-molecule DNA sensors and cages for transcription factors in vitro and in vivo - Crawford, R (2011)
Gene regulation is vital to the success of all living organisms. Understanding this complex process is crucial to our knowledge of how cells function and how in some cases they can lead to debilitating or even fatal disease. In this thesis I focus on a set of DNA-binding proteins known as transcription factors (TFs), proteins fundamental to the process of gene regulation at the level of transcription. I develop assays and techniques for the detection and quantitation of TFs in vitro and in vivo as well as a method for TF encapsulation and release. The advantages of the TF detection assays in this thesis are made possible through the use of single-molecule (sm) fluorescence. This methodology enables detection of individually labeled molecules allowing discrimination of sample heterogeneities inaccessible with ensemble techniques. Here I present two different TF assays based on two sm observables: relative probe stoichiometry and Förster resonance energy transfer (FRET). The first assay design, based on stoichiometry, detects TFs using TF-dependent coincidence of two distinctly labelled DNA ‘half-sites’. I demonstrate sensitive detection (~ pM) in solution and on surfaces, multiplexed detection of multiple TFs, and detection in cell lysates. A kinetic model of the system is also developed, verified experimentally and used to quantify TF concentrations without the need for a calibration curve. The second assay design, based on FRET, is a novel approach to TF detection using TFmediated DNA bending. TFs are detected by bending the sensor and monitored with FRET at the single-molecule or ensemble level. I demonstrate TF detection in purifed form and expressed in cell lysates. As this sensor was designed for use in vivo, methods to hinder nuclease degradation are explored. For TF detection in vivo, I describe a successful strategy to internalise fluorescently labeled molecules into live E.coli. Viability and internalisation efficiency are characterised and ensemble measurements with FRET standards are demonstrated. Importantly, sm FRET measurements in vivo are achieved opening many exciting possibilities. The FRET based TF sensor is then internalised as a step towards real-time in vivo monitoring of TF concentrations. Finally a system based on DNA nanotechnology is presented for the non-covalent encapsulation and release of TFs. Such a system could be delivered into a cell to alter levels of gene expression using external stimuli as inputs. We believe these tools will generate valuable information in the study of prokaryotic gene expression as well as providing a potential commercial avenue towards diagnostics.